Reformasi Kebijakan Penilaian Kinerja Pns: Sebuah Solusi Atau Masih Sekedar Formalitas Administrasi? - Rista Nur Farida; Benny Sigiro; Eunike Prapti Lestari Krissetyanti (Jurnal Administrasi Publik, 2025)
This study aims to examine the implementation of civil servant performance appraisal policy reform, particularly the transition from Government Regulation (PP) Number 46 of 2011 to PP Number 30 of 2019 and Ministerial Regulation of PANRB Number 6 of 2022. A descriptive qualitative approach was employed, using semi-structured interviews and direct observations. The study focuses on one deputy within a central government agency, with Edwards III’s implementation theory as the analytical framework. The findings found that performance appraisals remain a mere formality and have not yet functioned as meaningful tools for performance development. Three main issues support this conclusion: (1) feedback from supervisors tends to be generic and non-specific, making the appraisal process procedural rather than development; (2) the absence of clear and measurable performance indicators allows for subjective assessments; and (3) the existing incentive system is not fully fair or proportional to actual performance. Furthermore, the post-reform structure has shifted appraisal authority to higher-level officials, raising concerns about evaluation relevance and fairness. This study contributes to the limited literature on performance management reform in Indonesia’s public sector by identifying persistent implementation challenges that limit the intended impact of performance appraisal policies. The findings highlight the need to enhance appraiser capacity in delivering constructive feedback and to review existing regulations to ensure a fairer, more objective, and impactful performance appraisal system that promotes employee motivation and well-being. Given that this study was limited to one institution and employed a qualitative approach, the generalizability of the findings remains limited.